Assure II Alone and with Tacoma and Classic for Efficacy in Fallow - R. S. Currie; P. W. Geier (Kansas Agricultural Experiment Station Research Reports, 2022)
The objective of this trial was to compare Assure II (quizalofop) at two rates with or without tank mix partners for grass control in fallow. Assure II at either rate alone provided similar control of volunteer corn and barley. Corn control was 90% or more regardless of rating date with all herbicides except Assure II at 8.0 oz/a plus Classic (chlorimuron) at 42 days after treatment (DAT). Tacoma (fenoxaprop) at 3.5 or 5.4 oz/a added to Assure II at 8.0 oz/a improved barley control later in the season.
Keywords: Tank mixtures; postemergence; fallow; herbicide resistant; corn; barley